Lafoensia pacari A. St.-Hil.: Wound healing activity and mechanism of action of standardized hydroethanolic leaves extract. (12th June 2018) - Pereira, Lucas Olivo Martins; Vilegas, Wagner; Tangerina, Marcelo Marucci Pereira; Arunachalam, Karuppusamy; Balogun, Sikiru Olaitan; Orlandi-Mattos, Paulo Eduardo; Colodel, Edson Moleta; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological importance: Lafoensia pacari A. St.-Hil., (Lythraceae) is a native tree of Brazilian Cerrado and commonly known in Brazil as "mangava-brava". Its leaves are used in Brazilian folk medicine in wound healing, cutaneous mycoses, and in the treatment of gastritis and ulcers. Aim of the study: The present study was designed to evaluate the wound healing activity and mechanism of action of the hydroethanolic extract of Lafoensia pacari A. St.-Hil. leaves (HELp), and to advance in its chemical profiling. Materials and methods: HELp was prepared by maceration in 70% hydroethanolic solution (1:10, w/v). The phytochemical analyses were investigated using colorimetry and electrospray ionization/mass spectrometric detection (ESI-MS n ). Its in vitro cytotoxicity was evaluated in CHO-K1 and L929 cells, while the in vivo acute toxicity was performed in mice. The potential in vivo wound healing activity was assessed using excision and incision rat models and histopathology of the wounded skin (excision model) was carried out. The in vitro wound healing activity of HELp was demonstrated by scratch assay in L-929 cells, by measuring proliferation/migration rate and p-ERK 1/2 protein expression using western blot analysis. HELp's in vivo anti-inflammatory activity was evaluated by lipopolysaccharide (LPS) induced peritonitis in mice, along with the determination of nitric oxide (NO) and cytokines (TNF-α and IL-10) in the peritoneal lavages. Its potential in vitro antibacterial activity was performed using microbroth dilution assay, while in vitro antioxidant activities was by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical, and ferric reducing antioxidant power (FRAP) assays. Results: The phytochemical analysis of HELp revealed the presence of polyphenols with ellagic acid, punicalagin, punicalin, kaempferol, quercetin-3- O -xylopyranoside and quercetin-3- O -rhamnopyranoside being the most prominent. HELp showed no toxicity on CHO-k1 and L929 cell lines. Topical treatment with HELp (10 and 30 mg/g of gel) presented increased rates of wound contraction at all the days evaluated with complete wound re-epithelialization at 22.0 ± 1.5 ( p  < 0.05) and 21.7 ± 1.6 ( p  < 0.01) days, respectively. Topical application of HELp (10, 30 or 100 mg/g of gel) in incised wounds caused an increase in tensile break strength at all concentrations resulting in moderate re-epithelialization and neovascularization, increased cell proliferation an accelerated remodeling phase of the wound, in a manner comparable to standard drug (Madecassol ®, 10 mg/g). In the scratch assay with L929 cells, HELp (0.1 and 0.03 mg/mL) and PDGF (5 ng/mL) resulted in the increased proliferation/migration rate of fibroblasts and higher expression of p-ERK 1/2 protein. In LPS-induced peritonitis, HELp (100 and 200 mg/kg p.o.) decreased total leukocyte migration, comparable to the dexamethasone (0.5 mg/kg p.o.). In RAW 264.7 macrophages activated by LPS, HELp produced anti-inflammatory activity dependent on increased concentrations of IL-10, reduction in NO production, without altering the TNF-α levels. HELp also presented potent antioxidant activity in the DPPH and FRAP, but lacks in vitro antibacterial activity. Conclusion: The present study results support the popular use of the leaves of L. pacari in the treatment of wounds. Its wound healing activity is multi-targeted and involves inhibition of the proliferative and anti-inflammatory phases, antioxidant and positive modulation of the remodeling phase that might be involved different secondary metabolites, with emphasis on the ellagic acid, punicalagin, punicalin, kaempferol, quercetin-3- O -xylopyranoside and quercetin-3- O -rhamnopyranoside. Graphical abstract: fx1